Effectiveness of digitalization healthcare system in Malaysia during COVID-19 / Ros Faridah Hanim Roslan and Siti Sarah Hashim - Roslan, Ros Faridah Hanim; Hashim, Siti Sarah (2022)
As the country fights with the outbreak, healthcare systems are most vulnerable since they are given the responsibility with saving the lives of covid-19 patients while also providing essential health services to those who were not infected with the virus. The main purpose of this research is to study the level of use of digitization system among healthcare sectors, identify the elements that contribute to the effectiveness of digitization of health care system and also to recognize the impact of use of digitization in healthcare system. This research was conducted in Klang, Selangor with patients and medical practitioners from the Hospital Tengku Ampuan Rahimah Klang and Hospital Pantai Klang. This study revealed three important findings. First, the vast majority of those surveyed said they have used digital healthcare in their daily lives for health-related matters. Second, there is a relationship between “patient empowerment”, “patient satisfaction”, “multi-channel behaviour”, and “operational services efficiencies” towards the effectiveness of digitalization of healthcare sectors. Thirdly, digitalization of healthcare indeed brings a positive impact towards the people.